Part II: consensus statements and expert recommendations for BRCA-associated breast cancer in the Asia-Pacific region: clinical management - Park, Yeon Hee; Lee, Soo Chin; Singer, Christian F.; Balmaña, Judith; Dent, Rebecca Alexandra; Tan, Veronique Kiak-Mien; Mulansari, Nadia Ayu; Yusof, Mastura Md.; Que, Frances Victoria F.; Lu, Yen-Shen; Parinyanitikul, Napa; Pham, Cam Phuong; et al. (Frontiers in Oncology, 2025)
IntroductionExisting guidelines have practical gaps in decision and treatment sequencing for BRCA germline pathogenic variant breast cancers. This paper aims to develop clinical-practice consensus guidelines to address these gaps in the clinical management of BRCA germline pathogenic variants-associated breast cancer in the Asia-Pacific region.MethodsAn expert panel of 16 medical oncologists, geneticists, and breast cancer surgeons from the Asia-Pacific region arrived at 25 statements. The high level of consensus of statements was considered at ≥75%. A survey of 134 healthcare practitioners, breast cancer surgeons, geneticists, oncologists, molecular biologists/pathologists explored the real- world practices in the Asia-Pacific region.ResultsA consensus was reached for 80% of the statements (20/25) and aligned with the international guidelines. A significant gap was observed between real-world practices and the recommendations of the steering committee members in discussing contralateral risk reducing mastectomy with the patients as a part of standard practice, considering poly ADP-ribose polymerase inhibitor (PARPi) + immunotherapy for early triple negative breast cancer (eTNBC) patients with BRCA variants who don’t achieve pathological complete response after neoadjuvant chemotherapy + immunotherapy, use of adjuvant PARPi in patients with BRCA germline pathogenic variants in eTNBC who have achieved pathological complete response from neoadjuvant therapy, and preference for endocrine therapy + PARPi over endocrine therapy + cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) as escalated adjuvant treatment for BRCA pathogenic variants with high-risk hormone receptor positive/human epidermal growth factor receptor 2 negative (HR+/HER2-negative) early breast cancer.ConclusionTesting for BRCA germline pathogenic variants should be expanded to include all young patients with breast cancer. Patients with BRCA germline pathogenic variants should undergo genetic testing before surgery as it can impact surgical intervention decisions and further systemic treatment. The use of neoadjuvant platinum agents in chemotherapy increases the pathological complete response rate. Adjuvant PARPi is preferred over CDK4/6i as escalated treatment in patients who are HR+/HER2-negative.